18.5k views
1 vote
Can anyone help me solve this question

Can anyone help me solve this question-example-1
User Telos
by
4.6k points

1 Answer

2 votes

Answer:

(6, 3 )

Explanation:

Given the 2 equations

5x - y = 27 → (1)

5x + 4y = 42 → (2)

Multiplying (1) by - 1 and adding to (2) will eliminate the x- term, that is

- 5x + y = - 27 → (3)

Add (2) and (3) term by term to eliminate the x- term

5y = 15 ( divide both sides by 5 )

y = 3

Substitute y = 3 into either of the 2 equations and solve for x

Substituting into (2)

5x + 4(3) = 42

5x + 12 = 42 ( subtract 12 from both sides )

5x = 30 ( divide both sides by 5 )

x = 6

Solution is (6, 3 )

User Selva Ganapathi
by
4.5k points